Design Analysis of Bottle Leaktester Machine through DFMA Method - Mukhamad Fahmi; Dhika Aditya Purnomo; Anda Iviana Juniani (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
This article describes the design analysis process for bottle leak detection machine components using the Design for Manufacturing and Assembly (DFMA) approach. The Boothroyd-Dewhurst DFMA approach was used to verify existing design efficiency, handling ratios, and fitting ratios. SolidWorks is used to represent study objects in three dimensions. The results of this study, the assembly time for the existing design is 30,53 minutes, the manufacturing time is 20,19 minutes and the total cost is 1819,58. The DFA Index of a bottle leak detection machine is 13,3. The implementation of the DFMA method provides recommendations for design improvements with the aim of reducing manufacturing costs and improving design efficiency